Кипіння в мікро- і макроканалах (аналітичний огляд). Частина 2. - Кулінченко, Віталій Романович (My University, 2015)
Розглянутий екзотермічний процес передачі тепла в мікро або макроканал, який містить киплячу рідину і може враховувати будь-який з наступних випадків або будь-яку комбінацію цих випадків: процес часткового кипіння в мікроканалі з хімічною реакцією в суміжній реакційній камері; процес часткового кипіння в мікроканалі з хімічною реакцією в суміжному реакційному мікроканалі; процес часткового кипіння в мікроканалі з хімічною реакцією в суміжній реакційній камері, за допомогою чого температура каталізатора підвищується менш 10, 5, 3 C на довжині реакційної камери, а час реакційного контакту складає менше 300 мс. Consideration exothermic process of transmission of heat in mini or macro channel which contains a boiling liquid and can take into account any of the followings cases or any combination of these cases: process of the partial boiling in a micro channel with a chemical reaction in a contiguous reactionary chamber; process of the partial boiling in a micro channel with a chemical reaction in a contiguous reactionary chamber, whereby the temperature of catalyst rises less than on 10 °С, 5 °С, 3 °С on along length of reactionary chamber, and time of reactionary contact makes less than 300 ^s; process of the partial boiling in a micro channel together with the process of change of phase in a contiguous technological chamber, by virtue of what extension temperatures in a technological chamber makes less 10 °С; process of the partial boiling in a micro channel together with the process of mixing in a contiguous technological chamber, by virtue of what extension temperatures in the chamber of mixing makes less 5 °С; process of the partial boiling in a micro channel together with the process of fermentation in a contiguous technological chamber
Keywords: кафедра процесів і апаратів харчових виробництв; кипіння; тепловіддача; мікроканал; макроканал; boiling is heat emission; micro channel; macro channel